Rate of convergence of the Taylor series for some classes of analytic functions - Savchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We study the rate of convergence of the Taylor series for functions from the classes A Ψ H p, p = 1, ∞, in the uniform and integral metrics.